SOSIALISASI DAN APLIKASI TEKNOLOGI PEMUPUKAN BERIMBANG SPESIFIK LOKASI UNTUK MENINGKATKAN MUTU DAN HASIL TANAMAN KAKAO DI KECAMATAN SELEMADEG TABANAN - A.A. N., SUPADMA; DIBIA, I N.; BAGUS, I G.NGURAH (Buletin Udayana Mengabdi; Vol 8 No 1 (2009): Volume 8 No.1 – April 2009, 2012)
ABSTRACT Cacao plant at Subak Abian Buana Sari Dusun Megati Kelod, Desa Megati, Kecamatan Selemadeg Timur, Tabanan regency were relativelly new. The farmers did not understand cultivation and the exact fertilizer dosage for cacao plant in their locations. In this community servise , the teams transferred to the farmers some informations about soil fertility, balance fertilization dosage, spesific locations fertilization dosage for cacao plant, and demonstration plots balance fertilization spesific location for cacao plant at Subak Abian Buana Sari. The activity results that the farmers understand about soil fertility, balance fertilization, spesific location fertilization dosage for cacao plant and to observe demonstration plot balance fertilization for growth, development, and yields of cacao plant. The yields of cacao plant increased 88,89 % respectively compared to without demonstration.